Survey of fundamental motor skills of students 10-11 years old during the covid-19 pandemic - Aditya Bagus Setyawan; Irwan Setiawan; Dhedhy Yuliawan; Budiman Agung Pratama (Sriwijaya Journal of Sport, 2022)
This study aims to find out more about the application of good and bad physical activity to school-age children and the effect of physical education on fine motor skills in children. The research aims to determine the physical activity of basic motor skills in fifth grade students at State Elementary School Tugu Mantub District, Lamongan Regency during the Covid-19 pandemic period. This study uses a descriptive quantitative approach. The subjects were 5th graders at Tugu Elementary School, Mantup District, Lamongan Regency with 10 students (M: 6; F: 4). The instrument uses the Test of Gross Motor Development, second edition (TGMD-2). The data analysis used is descriptive. The results show that physical activity on the fundamental motor skills of fifth grade students is in the average category with a range of GMQ Standard scores of 90-110 at the Percentile score of 25-75.